Stromal fibroblasts shape the myeloid phenotype in normal colon and colorectal cancer and induce CD163 and CCL2 expression in macrophages - Stadler, Mira; Pudelko, Karoline; Biermeier, Alexander; Walterskirchen, Natalie; Gaigneaux, Anthoula; Weindorfer, Claudia; Harrer, Nathalie; Klett, Hagen; Hengstschläger, Markus; Schüler, Julia; Sommergruber, Wolfgang; Oehler, Rudolf; et al. (Cancer letters, 2021)
Colorectal cancer (CRC) accounts for about 10% of cancer deaths worldwide. Colon carcinogenesis is critically influenced by the tumor microenvironment. Cancer associated fibroblasts (CAFs) and tumor associated macrophages (TAMs) represent the major components of the tumor microenvironment. TAMs promote tumor progression, angiogenesis and tissue remodeling. However, the impact of the molecular crosstalk of tumor cells (TCs) with CAFs and macrophages on monocyte recruitment and their phenotypic conversion is not known in detail so far. In a 3D human organotypic CRC model, we show that CAFs and normal colonic fibroblasts are critically involved in monocyte recruitment and for the establishment of a macrophage phenotype, characterized by high CD163 expression. This is in line with the steady recruitment and differentiation of monocytes to immunosuppressive macrophages in the normal colon. Cytokine profiling revealed that CAFs produce M-CSF, and IL6, IL8, HGF and CCL2 secretion was specifically induced by CAFs in co-cultures with macrophages. Moreover, macrophage/CAF/TCs co-cultures increased TC invasion. We demonstrate that CAFs and macrophages are the major producers of CCL2 and, upon co-culture, increase their CCL2 production twofold and 40-fold, respectively. CAFs and macrophages expressing high CCL2 were also found in vivo in CRC, strongly supporting our findings. CCL2, CCR2, CSF1R and CD163 expression in macrophages was dependent on active MCSFR signaling as shown by M-CSFR inhibition. These results indicate that colon fibroblasts and not TCs are the major cellular component, recruiting and dictating the fate of infiltrated monocytes towards a specific macrophage population, characterized by high CD163 expression and CCL2 production. •CAFs as well as normal fibroblasts are critically involved in the recruitment of monocytes in colon and colon cancer.•CAFs induce a specific macrophage phenotype, which is characterized by high CD163 and CCL2 expression.•CAFs and macrophages significantly increase their CCL2 production upon co-culture, whereas tumor cells do not produce CCL2.•CCL2, CCR2, M-CSFR and CD163 expression was dependent on active M-CSFR signaling in macrophages.•High CCL2 levels in CAFs/macrophages were found in vivo in human CRC by dissection, scRNA-Seq and immunofluorescence.